2016
DOI: 10.5194/acp-16-5075-2016
|View full text |Cite
|
Sign up to set email alerts
|

Resolving ice cloud optical thickness biases between CALIOP and MODIS using infrared retrievals

Abstract: Abstract. Despite its importance as one of the key radiative properties that determines the impact of upper tropospheric clouds on the radiation balance, ice cloud optical thickness (IOT) has proven to be one of the more challenging properties to retrieve from space-based remote sensing measurements. In particular, optically thin upper tropospheric ice clouds (cirrus) have been especially challenging due to their tenuous nature, extensive spatial scales, and complex particle shapes and light-scattering charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
110
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 66 publications
7
110
1
Order By: Relevance
“…A MAPE of 100 % might seem high, but one should keep in mind that this translates into small absolute errors for such thin cirrus clouds. For the lower IOT CALIOP range, a similar scatter is observed between IOT CALIOP and modelled IOT from infrared radiances for thin cirrus clouds in Holz et al (2016). Figure 12 shows the density scatter plot with IWP CALIOP on the horizontal axis and IWP CiPS on the vertical axis (Fig.…”
Section: Cirrus Propertiesmentioning
confidence: 59%
See 1 more Smart Citation
“…A MAPE of 100 % might seem high, but one should keep in mind that this translates into small absolute errors for such thin cirrus clouds. For the lower IOT CALIOP range, a similar scatter is observed between IOT CALIOP and modelled IOT from infrared radiances for thin cirrus clouds in Holz et al (2016). Figure 12 shows the density scatter plot with IWP CALIOP on the horizontal axis and IWP CiPS on the vertical axis (Fig.…”
Section: Cirrus Propertiesmentioning
confidence: 59%
“…When the column optical thickness is derived for all cirrus-covered bins, the relative difference between CALIOP and CPL is only 2.2 % due to cancellation of opposing CALIOP effects. Holz et al (2016) recently showed that the single-layer IOT derived from unconstrained CALIOP retrievals is low biased with respect to a single-channel thermal/infrared IOT retrieval combining CALIOP/MODIS observations and forward radiative transfer modelling. The bias is shown to increase with increasing IOT.…”
Section: Output Data: Cirrus Properties From Caliopmentioning
confidence: 99%
“…There is increasing evidence that the ice particle model should contain some degree of surface roughness (Foot, 1988;Baran et al, 2001Baran et al, , 2003Ottaviani et al, 2012;van Diedenhoven et al, , 2013van Diedenhoven et al, , 2014Cole et al, 2013Cole et al, , 2014Holz et al, 2016). In particular, using an ensemble ice particle model, Baran and C.-Labonnote (2007) and Baran et al (2014) showed that featureless phase functions best fitted their multi-angle satellite measurements at solar wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Application of an unrealistic ice model, e.g., with only smooth (unroughened) surfaces, results in an overall global bias (Macke and Mishchenko, 1996;Yang et al, 2007Yang et al, , 2008bHolz et al, 2016) as well as seasonal biases (Zhang et al, 2009) in cloud property retrievals. The overarching goal of this paper is to gain a better understanding of the constraints in the microphysical parameters of global ice clouds using angular polarimetric observations and state-of-the-art light-scattering computational capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spectral consistency of visible/near-infrared and thermal infrared retrievals (Baran and Francis, 2004) was recently investigated by Liu et al (2014) and Holz et al (2016), who report that retrieved ice cloud optical thicknesses are more consistent when particles are roughened.…”
Section: Introductionmentioning
confidence: 99%